Effects of Calophyllum inophyllum fruit extract on the proliferation and morphological characteristics of human breast cancer cells MCF-7 - Perumal, Shanmugapriya; Yeng, Chen; Kanwar, Jagat Rakesh; Sasidharan, Sreenivasan (Elsevier, 2016)
Objective: To evaluate the antiproliferative activity of Calophyllum inophyllum (C. inophyllum) fruit extract against human breast cancer cells MCF-7. Methods: The cytotoxic effect of C. inophyllum fruit extract against MCF-7 cancer cells was evaluated through MTT and CyQuant assays for 24 h and the morphological investigation of treated MCF-7 cells was observed under optical microscope using Giemsa staining. Results: The cytotoxic effect of C. inophyllum fruit extract against MCF-7 cancer cells was evaluated through MTT and CyQuant assays simultaneously for 24 h after treatment, which demonstrated the inhibition of cell viability with the IC50 values of 19.63 μg/mL and 27.54 μg/mL, respectively. The preliminary time-based morphological investigation of MCF-7 cells treated with the IC50 value (23.59 μg/mL) of C. inophyllum fruit extract was observed under an optical microscopy via Giemsa staining, which exhibited prominent histological characteristics of apoptosis. Conclusions: This study clearly proved that the proliferation of human breast cancer cell MCF-7 was inhibited by C. inophyllum fruit extract resulted from the induction of apoptosis in MCF-7 cells.